Selective depletion of CD11c+CD11b+ dendritic cells partially abrogates tolerogenic effects of intravenous MOG in murine EAE. Issue 10 (October 2016) - Wang, Limei; Li, Zichen; Ciric, Bogoljub; Safavi, Farinaz; Zhang, Guang‐Xian; Rostami, Abdolmohamad
Abstract : Depletion of CD11c + CD11b + DC through their low expression of IA and costimulatory molecules as well as high expression of TGF‐β, IL‐27, and IL‐10 partially yet significantly blocked i.v. MOG‐induced suppression of murine EAE. CD11c + CD11b + DCs depletion also precluded i.v. autoantigen‐induced T‐cell tolerance. Abstract : Intravenous (i.v.) injection of a soluble myelin antigen can induce tolerance, which effectively ameliorates experimental autoimmune encephalomyelitis (EAE). We have previously shown that i.v. myelin oligodendrocyte glycoprotein (MOG) induces tolerance in EAE and expands a subpopulation of tolerogenic CD11c + CD11b + dendritic cells (DCs) with an immature phenotype having low expression of IA and co‐stimulatory molecules CD40, CD86, and CD80. Here, we further investigate the role of tolerogenic DCs in i.v. tolerance by injecting clodronate‐loaded liposomes, which selectively deplete CD11c + CD11b + and immature DCs, but not CD11c + CD8 + DCs and mature DCs. I.v. MOG‐induced suppression of EAE was partially, yet significantly, blocked by CD11c + CD11b + DC depletion. While i.v. MOG inhibited IA, CD40, CD80, CD86 expression and induced TGF‐β, IL‐27, IL‐10 production in CD11c + CD11b + DCs, these effects were abrogated after injection of clodronate‐loaded liposomes. Depletion of CD11c + CD11b + DCs also precluded i.v. autoantigen‐induced T‐cell tolerance, such as decreased production of IL‐2, IFN‐γ, IL‐17 and numbers of IL‐2 +, IFN‐γ +, and IL‐17 + CD4 + T cells, as well as an increased proportion of CD4 + CD25 + Foxp3 + regulatory T cells and CD4 + IL‐10 + Foxp3 − Tr1 cells. CD11c + CD11b + DCs, through low expression of IA and costimulatory molecules as well as high expression of TGF‐β, IL‐27, and IL‐10, play an important role in i.v. tolerance‐induced EAE suppression.